Mengimplementasikan Ekowisata Menjadi Strategi Pengelolaan Manajemen Pada Air Terjun Blangsinga - Gagih Pradini; Dipateruna Awaloedin; Anisa Putri Kusumaningrum; Putri Aulia Ardani; Putri Aisyah Prisilia (Jurnal Ilmiah Wahana Pendidikan, 2023)
The tourism sector in this era of globalization has made many changes and has experienced rapid development. This is all aimed at increasing the quality and quantity of the destination. Therefore, it is necessary for the tourism sector to implement an ecotourism system for tourism objects that are owned to be responsible for the preservation of unspoiled areas, provide economic benefits and maintain cultural integrity for the local community. This research is related to the development of the Blangsinga waterfall tourist area into an ecotourism area. Around the waterfall area there are many adequate places, but around the waterfall itself there are still many shortcomings in terms of supporting facilities and the absence of insightful activities. Methods This research was conducted qualitatively, with reference to the theory of ecotourism and sustainable tourism. In order to obtain comprehensive data. The focus of this research is on Blangsinga Waterfall, Saba Village, Blahbatuh District. Data collection is carried out through interviews and academic literature studies that are able to examine and dig deeper by taking into account the background, socialization patterns and implications for local communities and foreign tourists.